2018
DOI: 10.25134/ieflj.v4i1.888
|View full text |Cite
|
Sign up to set email alerts
|

An Interpersonal Meaning Analysis of Ahok�s Blasphemy Case in Online News Portals

Abstract: This research presents an interpersonal meaning analysis of two online news concerning Ahok�s blasphemy case in the two online news portals. The two selected news coming from The Jakarta Post and Republika.co.id were analyzed to find out the mood types and to describe the underlying reason of the news from the differences of modality system. This descriptive qualitative research involved the analysis of mood and modality types of clauses identified. As results, it shows that the interpersonal meaning was appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Portals" by Kartika & Wihadi (2018), which discussed the mood and modality in online news articles. This descriptive qualitative research showed that only one mood and modality type appeared in the articles, namely indicative, declarative type, and the modalization is probability type.…”
Section: First "An Interpersonal Meaning Analysis Of Ahok's Blasphemy...mentioning
confidence: 99%
“…Portals" by Kartika & Wihadi (2018), which discussed the mood and modality in online news articles. This descriptive qualitative research showed that only one mood and modality type appeared in the articles, namely indicative, declarative type, and the modalization is probability type.…”
Section: First "An Interpersonal Meaning Analysis Of Ahok's Blasphemy...mentioning
confidence: 99%
“…mood types since the text is in a written form (Yuliana & Imperiani 2017;Kartika & Wihadi;(2018);and Anggi, 2018).…”
Section: Future Scenariosmentioning
confidence: 99%
“…Furthermore, some studies on language crime also explored blasphemy (Kartika & Wihadi, 2018;Syahid et al, 2021) and hate speech from a political perspective (Iswatiningsih et al, 2019;Mintowati et al, 2019;Wulandari, 2022). Kartika & Wihadi (2018) Syahid et al (2021) analyzed the blasphemy element in somebody's speech on social media, and the researcher took the data from the Medan District Court. Iswatiningsih et al (2019) discussed the hate speech spoken by the supporters of Indonesian presidential candidates on Facebook and Instagram.…”
Section: Introductionmentioning
confidence: 99%